Assessment of the Safety and Efficacy of Prolapsed Orbital Fat Resection During Involutional Entropion Repair. Issue 1 (January 2020) - Prendes, Mark A.; Geng, June; Ediriwickrema, Lilangi S.; Areephanthu, Christopher; Burchell, Patrick; Kikkawa, Don O.; Nunery, William R.; Korn, Bobby; Harold Lee, H. B.
Abstract : Purpose: To assess the recurrence rate of involutional entropion in patients treated with a combined approach including a modified Bick procedure, excision of preseptal orbicularis muscle, and conservative resection of prolapsed orbital fat. Methods: A retrospective chart review of patients undergoing repair of involutional entropion with the combined procedure including orbital fat resection and a second group with standard entropion repair without orbital fat resection was performed. Only patients with follow-up greater than 6 months were included in the study. Results: Seventy eyelids of 54 patients met all inclusion criteria for the combined procedure group over a 9-year period from 2008 to 2016. Average follow-up was 46.9 months. There was a documented recurrence of entropion in 1 eyelid during the follow-up period (1.4%). The remaining 69 cases had successful subjective and objective results without need for any additional procedures. In the group undergoing entropion repair without fat resection, 22 eyelids of 19 patients had the required follow-up period with a recurrence rate of 4.5% ( p > 0.05). Conclusions: The authors demonstrate good surgical success with a combined approach of a modified Bick procedure, preseptal orbicularis excision, and conservative orbital fat resection. Conservative fat resection during entropion repair was found to be safe, and the combined procedure was found to be effective with a rate of recurrent entropion of 1.4% on extended follow-up. The authors propose that orbital fat prolapse contributes to the mechanics of involutional entropion and that conservative orbital fat resection during surgical repair of entropion can be done safely, resulting in low recurrence rates.